Navigating the map of environmental-policy narratives and its influence within the conservation network of the Colombian-Peruvian Amazon - Gonzalez-Rodriguez, Carlos Eduardo; Buitrago-Bermúdez, Oscar; Gonzalez, Carolina; Castillo-Rivera, Johana Marcela; Le Coq, Jean-Francois (Springer Science+Business Media, 2026)
The Colombian-Peruvian Amazon's global socio-ecological relevance attracts multiple organizations and technologies related to cooperation and environmental governance, configuring a complex network of interactions, relationships, and relational structures. This case study seeks to provide clarity on the complex functioning of the cooperation network in the Amazon biome, composed of institutional and technological nodes. It identified 17 thematic environmental narratives, their patterns of concordance by node (entities/institutions operating within the network), and how they influence inter-network links. Studying cooperating networks in dynamic contexts is made complex by progressive and diverse environmental threats, economic challenges, and barriers to accessing information. The article proposes a methodological approach to untangling these complexities, leveraging (a) social network analysis; (b) web scraping for data collection; (c) text mining to categorize narrative themes by node; and (d) network modeling using Exponential Random Graph Models. We propose and evaluate hypotheses on the influence of narrative concordance, contribution, homophily, and environmental-governance internal structural patterns that are important in creating network links. Study results indicate three dominating narratives: Research & Education, Communities, and Policy, revealing a higher distribution, average contribution, and significance for these discourses. Additionally, international nodes contribute predominantly to Research and Technology topics, surpassing Colombian-Peruvian nodes, suggesting a pattern of influence over these network themes. Lastly, we identify opportunities for improving system interventions for slowing the Amazon biome's degradation, composed of a diversified, well-integrated cooperation network, and underscoring the need for environmental-policy frameworks that actively integrate local perspectives and capacities, while leveraging international networks to bridge regional limitations.